2013
DOI: 10.1371/journal.pone.0057406
|View full text |Cite
|
Sign up to set email alerts
|

Rat Macrophage C-Type Lectin Is an Activating Receptor Expressed by Phagocytic Cells

Abstract: Macrophage C-type lectin (MCL) is a membrane surface receptor encoded by the Antigen Presenting Lectin-like gene Complex (APLEC). We generated a mouse monoclonal antibody for the study of this receptor in the rat. We demonstrate that rat MCL is expressed on blood monocytes and neutrophils, as well as on several tissue macrophage populations, including alveolar and peritoneal cavity macrophages. We also demonstrate MCL expression on a subset of resident spleen macrophages. Immunohistochemistry analysis of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 36 publications
3
48
1
Order By: Relevance
“…Spleen extraction and histologic preparation were performed as described elsewhere (Lobato-Pascual et al, 2013). Briefly, adult mice were anesthetized using 5% isoflurane and then perfused using 4% paraformaldehyde, pH 7.2.…”
Section: Methodsmentioning
confidence: 99%
“…Spleen extraction and histologic preparation were performed as described elsewhere (Lobato-Pascual et al, 2013). Briefly, adult mice were anesthetized using 5% isoflurane and then perfused using 4% paraformaldehyde, pH 7.2.…”
Section: Methodsmentioning
confidence: 99%
“…Another study found that MCL interacts with FcRγ in rat myeloid cells but not in transfected non-myeloid cells, suggesting that the interaction is indirect (Lobato-Pascual et al, 2013a). However, subsequent studies have shown that MCL-FcRγ interaction and signaling requires Mincle and formation of MCL-Mincle heterodimers (Lobato-Pascual et al, 2013b).…”
Section: C-type Lectin Receptorsmentioning
confidence: 99%
“…In search for an appropriate cell line to mimic this phenomenon, we screened a number of rat cells retrieved from different sources. One of these cell lines was the RmW, originally derived as a side‐product of a T cell leukemia cell line (Roser Leukaemia) . The RmW cell line has not previously been fully described and therefore, was characterized by using an array of rat mAb (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The myeloid cell line RmW originates from PVG ( RT1 c haplotype) rat spleen as a side product during the generation of an in vitro passageable variant of the in vivo‐restricted Roser leukemia (a rat T cell leukemic cell line) . The phenotype of this cell line was determined by flow cytometry using a panel of mAb specific for the rat (listed in Table ).…”
Section: Methodsmentioning
confidence: 99%